MENAKAR PELUANG PELINDUNGAN INDIKASI GEOGRAFIS PADA BIDANG JASA DALAM KERANGKA HUKUM INDONESIA: SEBUAH DIAGNOSA AWAL - Muh. Ali Masnun (Dialogia Iuridica, 2021)
The protection of geographical indications in Indonesia is still limited to the goods sector, but not yet for the service sector. The purpose of this study is to analyze the opportunities for the protection of geographical indications in the service sector within the legal framework in Indonesia. This research is a doctrinal research using a conceptual and statute approachs. The results of the study can be concluded that the opportunity for protection of geographical indications in the service sector is very good with an argument consisting of 4 aspects, including the provisions of the TRIPS agreement which are open, the potential for uniqueness of the region. based services, protection through the relative geographical indications still has weaknesses, and protection through communal intellectual property (traditional knowledge) is also relatively weak. The opportunities for the protection of geographical indications are also very relevant to several legal protection theories, including: predictive and anticipatory legal protection theory, integrative and coordinative theory, and social ownership theory.